Perbandingan Dinamika Penggunaan Jilbab di Masa Orde Baru dan Reformasi - Pujiati, Pujiati (Perkumpulan Program Studi Sejarah Se-Indonesia, 2023)
Throughout Indonesia's history, especially during the New Order and Reformation eras, Muslim women's head covering usage has changed. This study looks at the variations in head covering usage in Indonesia under the New Order and Reformasi. The methodologies used to conduct this study were qualitative. Data are collected by observation, literature study, and recordkeeping. The study's findings demonstrate that the creation of the headscarf eventually serves a number of significant purposes because the circumstances in which they are made, as well as the players and interests associated with them, are extremely varied. During the New Order era, the Indonesian government outlawed Muslim women from donning the headscarf, which resulted to pupils being dismissed from school. Despite the ban's fierce opposition from Muslims, it was changed for stability. The headscarf is now regarded as a human right in the contemporary reform age, and Muslim women's clothing is regarded as art and a representation of their individuality.